The Fading Away of Frontiers during Neoliberalism: Work, Crime and the Law among Argentinean Youth - Kessler, Gabriel (2015)
The emergence of a segment of the population that alternates legal and illegal acts to survive during the nineties, thus establishing a special relationship with the law, is analyzed in this article. It shows the emergence of a sector of the population that, neither worker nor "professional criminal," survives on the basis of a combination of legal and illegal activities in a period in which work was scarce. Following a sector containing statistical data, the relationship between crime and work is analyzed, followed by a section on the rationale underlying the young people's acts, the symbolic space occupied by the law, peer group relations and, finally, relations with the police.